TOPONYMY OF THE CITIES OF THE REPUBLIC OF KARAKALPAKSTAN AND THE KHOREZM REGION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article is devoted to the study of the toponymy of the cities of the Republic of Karakalpakstan and the Khorezm region. The study analyzes the origin of the names, historical development and linguistic results of the following cities. The main objectives of the article are to develop the naming process in the region, to reveal the ethnological foundations of the city and its connection with historical and geographical support. With this, the influence of toponymy on cultural, ethnic composition and linguistic characteristics is also studied.